2020
DOI: 10.1364/optica.390186
|View full text |Cite
|
Sign up to set email alerts
|

Label-free biochemical quantitative phase imaging with mid-infrared photothermal effect

Abstract: Label-free optical imaging is valuable in biology and medicine with its non-destructive property and reduced optical and chemical damages. Quantitative phase (QPI) and molecular vibrational imaging (MVI) are the two most successful label-free methods, providing morphology and biochemistry, respectively, that have pioneered numerous applications along their independent technological maturity over the past few decades. However, the distinct label-free contrasts are inherently complementary and difficult to integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
96
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(108 citation statements)
references
References 41 publications
(160 reference statements)
3
96
0
Order By: Relevance
“…Only ADRIFT-DH clearly visualizes the signal localization, especially at the nucleus, nucleoli and some particles indicated by the arrows in Fig. 5a, which could represent the richness of proteins 13 .…”
Section: Dynamic-range-expanded Mir Photothermal Qpi Of a Live Biologmentioning
confidence: 80%
See 3 more Smart Citations
“…Only ADRIFT-DH clearly visualizes the signal localization, especially at the nucleus, nucleoli and some particles indicated by the arrows in Fig. 5a, which could represent the richness of proteins 13 .…”
Section: Dynamic-range-expanded Mir Photothermal Qpi Of a Live Biologmentioning
confidence: 80%
“…To illustrate the advantage of ADRIFT-QPI, we apply this technique to MIR photothermal QPI [10][11][12][13] . MIR photothermal QPI is a recently developed molecular vibrational imaging method, where the refractive index change of the sample caused by the absorption of MIR pump light is detected through the OPD change of visible Figure 4a shows the pump-OFF-state OPD images obtained by conventional DH and ADRIFT-DH.…”
Section: Dynamic-range-expanded Mir Photothermal Qpi Of Microbeadsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pleitez et al ( 32 ) demonstrated mid-IR photoacoustic microscopy with broad biomedical applications for monitoring carbohydrates, lipids, and proteins in cells and tissues. The Ideguchi group ( 62 ) recently reported the MIP quantitative phase imaging with depth-resolved capability and extended dynamic range ( 63 ).…”
Section: Introductionmentioning
confidence: 99%